PENGARUH PENGGUNAAN LEMBAR KERJA PESERTA DIDIK BERBASIS APLIKASI QUIZIZZ TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD INPRES PANNAMPU 3 - Ilhmi Zahrani, Nurul; Ma'ruf; Anisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using Quizizz-based student worksheets on the learning outcomes of fourth-grade students. This is a quantitative study using a quasi-experimental design. The independent variable in this study is the use of Quizizz-based student worksheets, while the dependent variable is learning outcomes in Natural Sciences. The study population comprises all fourth-grade students at SD Inpres Pannampu 3, with a sample of 44 students selected using Cluster Random Sampling, where the experimental and control groups were randomly assigned from the entire fourth-grade class. The data collection techniques used included tests (pretest and posttest) consisting of 20 multiple-choice questions, teacher and student observation sheets, and documentation that had passed instrument validation. The data in this study were analyzed using instrument validation techniques, descriptive statistical analysis, and inferential statistics with hypothesis testing. The results indicate that the use of Quizizz-based Student Worksheets has an effect on the IPAS learning outcomes of fourth-grade students at SD Inpres Pannampu 3. This is evidenced by the control group’s posttest average score of only 63.18, whereas the experimental group’s posttest average score reached 85.91. Based on the results of the independent samples t-test, the significance value (two-tailed) under the assumption of equal variances was < 0.001, which is far smaller than the significance level of 0.05; in other words, H₀ is rejected and H₁ is accepted, meaning that the use of Quizizz-based Student Worksheets has an effect on the IPAS learning outcomes of fourth-grade students at SD Inpres Pannampu 3.